Pengaruh Etika Bisnis Islam dan Bauran Pemasaran terhadap Loyalitas Nasabah dengan Keputusan Menjadi Nasabah Sebagai Variabel Intervening (Studi pada BPD Jateng Syariah, BRI Syariah dan Bank Muamalat) di Kota Semarang - Salam, Abdus; Habibah, Muzayyidatul (Universitas Islam Negeri Sunan Kudus, 2021)
These study aims to determinew the system from the application of Marketing Mix and Islamic Business Ethicss there is Customer loyalty in Islamic Banking (BRI Syariah, Bank Jateng Syariah and Bank Muamalat) in Semarang City. By using the variables of Marketing Mix and Islamic Business Ethics as Exogenous Variables and Customer Loyalty as Endogenous Variables, besides that, intervening variables are also used to seasure the mediating effect of exogenous to endogenousfactors. Sampling using purposive sampling. The data used is primary data from 3 Islamic Banking customers who are 100 respondents. The results of the study explain that first, the Marketing Mix affects the decision to becomea customer. Second, Islamic Business Ethics influences the decision to became a customer. Third, Marketing Mix has an effect on Customer Loyalty. Fourth, Islamic Business Ethics has no effect on Customer Loyalty. Fifth, the decision to become a customer affects customer loyalty. Sixth, the decision to become a customer is able to mediate between marketing and customer loyalty. Seventh, the decision to become a customer is unable to mediate Islamic Business Ethics on Customer Loyalty.